2016
DOI: 10.5430/ijba.v7n5p1
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Tourism Satisfaction and Destination Image for Leisure Travelers Who Use Macau Low-Cost Carriers

Abstract: The purpose of this study is to enhance the understanding of the relationship between the Low-Cost Carriers (LCC) leisure travelers' satisfaction and the destination images of Macau. Moreover, the researchers plan to provide suggestions for a sustainable development of Macau low-cost carriers. The LCC provide visitors planning to travel to Macau as the final destination cheaper and efficient choices. On the other hand, the LCC offer the visitors who were not selected Macau to be their final destination more ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Numerous studies have also explored factors that impact events tourism destination selection, such as "host site cost." Vassiliadis et al [ 151 ], "accessibility", and "Favorable currency exchange rates" as Ratten et al [ 132 ], and "service quality of accommodation facilities" [ 147 , 157 ]. The authors of this paper found that from a perspective of people's decision-making processes has yet to be studied, creating a gap in the conceptualization and modelling of tourists' behaviour connected to events travel [ 21 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have also explored factors that impact events tourism destination selection, such as "host site cost." Vassiliadis et al [ 151 ], "accessibility", and "Favorable currency exchange rates" as Ratten et al [ 132 ], and "service quality of accommodation facilities" [ 147 , 157 ]. The authors of this paper found that from a perspective of people's decision-making processes has yet to be studied, creating a gap in the conceptualization and modelling of tourists' behaviour connected to events travel [ 21 , 41 ].…”
Section: Introductionmentioning
confidence: 99%